Educação e trabalho infantil no comércio informal nas embarcações que navegam no Rio Tajapuru, Arquipélago do Marajó-PA, na visão de pais e professores - SILVA, Rosicley Silva e (2019)
The present Work of Conclusion of Course aimed to analyze the influence of the work with sales and exchanges in the stern of the rafts in the river Tajapuru in the process of teaching learning of the children who carry out these commercial exchanges. As specific objectives we seek to describe the living conditions of the family and the work practice related to the school context of the child; and to identify the influences of work activities in the educational formative process of riverside children of the Tajapuru River. This research proposes to answer the following main question: how do riverine families and their children give meaning to sales and commercial work in the stern of the rafts in the river Tajapuru, linking it to the teaching process of learning in the school of these children who carry out these commercial exchanges? The guiding questions related to this research problem were: what are the living conditions of the families researched and the work practices that relate to the children's school context? What are the influences of work activities on the educational formative process of riverine children in the Tajapuru River? For its accomplishment, a bibliographical research was initially carried out. Subsequently, the qualitative approach was chosen, and the type of research was the case study in a primary school in the rural area of the municipality of Breves-PA. The technique of data collection was the semi-structured interview. We interviewed 03 teachers and 03 families / guardians with children enrolled in the researched school. In order to base the discussions of this research, we use propositions from Azambuja (2004), Rizzini and Pilotti (2009), Souza (2011), Vieira (2011), Lima (2012) and Guedes (2018). As results, we understand that the families 'living conditions are difficult, creating a context in which the work carried out by children and adolescents students emerges as a path that can help improve the condition of life, even with consequences for the students' school life. We also conclude that there are several consequences on the educational development of these individuals, caused by the work done by the students, such as lack of classes, difficulties with school subjects; difficulties with extraclass activities; loss of evaluative activities and, as a result, low income; school dropout and retention.